2007
DOI: 10.1590/s0102-311x2007000100019
|View full text |Cite
|
Sign up to set email alerts
|

Gravidez na adolescência: perfil sócio-demográfico e comportamental de uma população da periferia de São Paulo, Brasil

Abstract: Com objetivo de identificar o perfil sócio-demográfico e comportamental de gestantes adolescentes, foram entrevistadas mil adolescentes, admitidas entre 24 de julho de 2001 e 27 de novembro de 2002, em um hospital municipal de São Paulo, Brasil, correspondendo a 24,3% das internações para resolução da gestação. Setenta (7%) adolescentes foram admitidas para curetagem pós-abortamento e 930 (93%), para parturição, com idade média de 17 ± 1,5 anos. A maioria (72,4%) residia próximo ao hospital e 93% pertenciam às… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
2
125

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(171 citation statements)
references
References 20 publications
3
41
2
125
Order By: Relevance
“…Many of our results, especially those related to age at sexual initiation and to the rates of condom use, confirmed those found by the GRAVAD Survey 16 and by other surveys on adolescents' sexual behaviour in Brazil. The rates of teenage pregnancy we found in our study are also similar to those found for rural areas and for impoverished suburbs of metropolitan areas in Brazil 8,18 and Latin America. 10 In a study of the sociodemographic behavioural profile of low-income teenagers in a very poor neighbourhood in São Paulo, the largest Brazilian city, Chalem et al 18 found that 27% of 1,000 girls included in their study had been pregnant at least once.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Many of our results, especially those related to age at sexual initiation and to the rates of condom use, confirmed those found by the GRAVAD Survey 16 and by other surveys on adolescents' sexual behaviour in Brazil. The rates of teenage pregnancy we found in our study are also similar to those found for rural areas and for impoverished suburbs of metropolitan areas in Brazil 8,18 and Latin America. 10 In a study of the sociodemographic behavioural profile of low-income teenagers in a very poor neighbourhood in São Paulo, the largest Brazilian city, Chalem et al 18 found that 27% of 1,000 girls included in their study had been pregnant at least once.…”
Section: Discussionsupporting
confidence: 89%
“…The rates of teenage pregnancy we found in our study are also similar to those found for rural areas and for impoverished suburbs of metropolitan areas in Brazil 8,18 and Latin America. 10 In a study of the sociodemographic behavioural profile of low-income teenagers in a very poor neighbourhood in São Paulo, the largest Brazilian city, Chalem et al 18 found that 27% of 1,000 girls included in their study had been pregnant at least once. Using the GRAVAD data set, Dias and Aquino 19 have shown that from a total of 4,634 teenagers from different social backgrounds interviewed, 18% of the girls and around 6% of the boys had experienced parenthood during adolescence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nos Estados Unidos, em 2001, a proporção de gravidez em mulheres de 10 a 19 anos foi de 4,1%, apresentando redução de 24% desde 1990 22 .…”
Section: Discussionunclassified
“…A educação das adolescentes pode fortalecê-las a decidir sobre suas próprias vidas e desenvolver um comportamento planejado 9,13,22 . Quanto menor a escolaridade, maior a dificuldade de entendimento da necessidade de cuidados especiais no decorrer da gravidez, levando ao inicio tardio e ausência de pré-natal, alimentação inadequada e hábitos e vícios incompatíveis com a gravidez 25 .…”
Section: Discussionunclassified